Evidence for a mid-Holocene drowning from the Atacama Desert coast of Chile. (April 2022) - Andrade, Pedro; Goff, James; Pearce, Richard; Cundy, Andrew; Sear, David; Castro, Victoria
Abstract: Coastal archaeological communities were exposed to numerous risks associated with living in their liminal environment. Many of the problems faced by these populations have been recorded and interpreted through their skeletal remains, but death by drowning in saltwater is not easy to recognise and as such is invariably either ignored, inferred, or discounted as a possible cause of death. Here we develop and test an enhanced microscopic marine fingerprinting methodology to determine the death by drowning of a ∼5000 year old coastal hunter-gatherer from the hyperarid coast of northern Chile. Through the application of this forensic method, we were able to detect the presence of a range of exogenous microscopic material that allows us to postulate his death because of drowning in the nearshore environment. This methodology has the potential to greatly enrich our understanding of past human-environment interactions not only in northern Chile but also around the world's coastlines. How pervasive was drowning in prehistory particularly along an active, tectonic margin exposed to palaeotsunamis and extreme ENSO-related palaeostorms? Highlights: Skeletal remains of a ∼5000 year old fisherman found in a coastal mass burial. Modified 'Diatom Test' performed on bone marrow of large bones. Exogenous microscopic material indicates death by drowning. Microscopic mineral grain size range indicates no contamination of bone marrow. Combined archaeological and geological data indicated nearshore drowning.